Generation of novel neuroinvasive prions following intravenous challenge. (5th July 2018) - Aguilar‐Calvo, Patricia; Bett, Cyrus; Sevillano, Alejandro M.; Kurt, Timothy D.; Lawrence, Jessica; Soldau, Katrin; Hammarström, Per; Nilsson, K. Peter R.; Sigurdson, Christina J.
Abstract: Prions typically spread into the central nervous system (CNS), likely via peripheral nerves. Yet prion conformers differ in their capacity to penetrate the CNS; certain fibrillar prions replicate persistently in lymphoid tissues with no CNS entry, leading to chronic silent carriers. Subclinical carriers of variant Creutzfeldt–Jakob (vCJD) prions in the United Kingdom have been estimated at 1:2000, and vCJD prions have been transmitted through blood transfusion, however, the circulating prion conformers that neuroinvade remain unclear. Here we investigate how prion conformation impacts brain entry of transfused prions by challenging mice intravenously to subfibrillar and fibrillar strains. We show that most strains infiltrated the brain and caused terminal disease, however, the fibrillar prions showed reduced CNS entry in a strain‐dependent manner. Strikingly, the highly fibrillar mCWD prion strain replicated in the spleen and emerged in the brain as a novel strain, indicating that a new neuroinvasive prion had been generated from a previously non‐neuroinvasive strain. The new strain showed altered plaque morphology, brain regions targeted and biochemical properties and these properties were maintained upon intracerebral passage. Intracerebral passage of prion‐infected spleen re‐created the new strain. Splenic prions resembled the new strain biochemically and intracerebral passage of prion‐infected spleen re‐created the new strain, collectively suggesting splenic prion replication as a potential source. Taken together, these results indicate that intravenous exposure to prion‐contaminated blood or blood products may generate novel neuroinvasive prion conformers and disease phenotypes, potentially arising from prion replication in non‐neural tissues or from conformer selection.